Sondagem molecular da superfície de biocarvões de casca de café modificados com óxido de grafeno e boro - Pinheiro, Ísis Maria Vilas Bôas (2021)
Biochars are materials with a high potential to help in the solving of some environmental problems. However, they are complex materials that need thorough studies to evaluate how they work in nature, especially when it comes to their absorbing capabilities. That is why this study was aimed to evaluate the absorbing characteristics of coffee husk biochars modified with graphene oxide and boron (BCOG) put in different pyrolysis temperatures (400, 550, 700, 900°C), regarding molecules of dicumarol and 4-hydroxycoumarin that acted like guideline molecules to evaluate the absorbing capabilities of the materials studied. Balance tests on molecule’s absorption were held evaluating the effect of environment’s ph. and ionic strength. The results showed that the biochar’s structural transformation associated to the pyrolysis temperature has more influence over absorbing capabilities than the electrostatic forces in the system. The dicumarol absorption was 5 times bigger than the 4-hydroxycoumarin for biochars obtained in higher pyrolysis temperature, showing the importance of hydrophobic interactions to the absorbing process. At last, the analysis of 4-hydroxycoumarin absorption isotherms informed that the absorption capability increases following the order BCOG400 ≈ BCOG500 > BCOG750 > BCOG900 in low equilibrium concentrations, being that for higher equilibrium concentrations BCOG400 showed greater absorbing capability.